TEACHING WRITING RECOUNT TEXT THROUGH CLUSTERING TECHNIQUE AT 10Th GRADE OF MA DDI PULAU KIJANG - Rian Juanda; Samsul Amri; Syafrizal (Program Studi Pendidikan Bahasa Inggris, 2022)
This study analysed teaching writing recount text through clustering technique, writing is the process of using symbols to communicate and recount is speaking or writing about past events. Students need to write their recount as final test at tenth grade in curriculum 2013, Not easy to make a good recount text it has generic structure, characteristic and students need much vocabulary to choose to make their sentences on recount text much better. The fact students has felt harder to make a recount text they may miss some of the events that are supposed to be recounted and gotten stuck in the middle. To solve their problem researcher brings clustering technique to make their recount text easier. The main purpose of this thesis is to find out the effect of using clustering technique towards student ability in writing recount text at tenth grade of MA Darud Da’wah Wal-Irsyad Pulau Kijang. This thesis is categorized as experimental research because it is intended to know the effect of clustering technique towards student ability in writing recount text at tenth grade of MA Darud Da’wah Wal-Irsyad Pulau Kijang, these subject of research were taken 1 class (tenth IPS) it contains 23 students. The research instrument that used in this thesis is the writing recount text test. There are two kinds of tests: pre-test and post-test used to find out whether there is a significant effect for students in that class. After the data had been collected by using test it was found that the pre-test average is 49.89 categorized E and post-test is 74.02 categorized C. the obtained t-observe was 4.19, whereas the t-table 2.074 for 5% and 2.819 for 1%, it means t-observe is higher than t-table (2.074 < 4.19 > 2.819) Ha was accepted while Ho was rejected. Since t-observe score was higher than t-table clustering technique is effective as media in students' ability in writing recount text at tenth grade of MA Darud Da’wah Wal-Irsyad Pulau Kijang. Based on the findings, the writer concluded that there is a significant effect of using the clustering technique as one of the media teaching writing recount text at tenth grade of MA Darud Da’wah Wal-Irsyad Pulau Kijang.